General Geology of Kijal area in Terengganu with emphasize on Characterization of Carbonaceous Slate - binti Abu Bakar, Nur Aimi Asyiqin (Universiti Teknologi PETRONAS, 2016)
Kijal area is located on the southern part of Terengganu, where Sungai Perlis Beds are exposed on the surface. Sungai Perlis Bed that consists of metasediments, such as slate, carbonaceous slate and quartzite has been found in the study area. Granite, which might be a part of the Eastern Granite Belt, is also found in Kijal area. Geological fieldwork has been conducted to construct geological map of Kijal area, petrographic study (thin section) for identifying the mineral of the rock samples and chemical analyses (TOC analysis, XRF analysis and SEM/EDX analysis) have been conducted to characterize the carbonaceous slate. Based on petrographic study, the rock types of the study area has been confirmed, which consists of slate, quartzite and granite. As for characterization of carbonaceous slate, it can be characterised according to their sample colour as well as chemical contents. The colour of the carbonaceous slate ranges from grey to black. In terms of chemical contents, the TOC content of carbonaceous slate in Kijal area ranges from 0.223% to 8.81%. The organic carbon content increases towards the eastern part of Kijal area suggests that the eastern part might be the deepest part of the shallow marine environment and have good potential for source rock. In terms of oxides, carbonaceous slates are dominant in SiO2, Al2O3, and K2O, which indicated that the carbonaceous slate are controlled by silicate minerals, particularly quartz, have abundance of feldspar and clay minerals (kaolinite) as well as it is related to the presence of authigenic Kfeldspar. Whereas, the low concentration of MgO and CaO suggests that the samples did not associate with carbonate or dolomitization.